Fluxograma para o cuidado à saúde bucal no Sistema Único de Saúde em Belém/PA - NAZARETH, Izabelly Christini André (2025)
The Integrality in Health of dentistry services, offered by the Unified Health System, should guarantee the continuity of assistance in units close to the dwellings of the population. Objective: Construct workflow for the oral health in the city of Belém/PA. Methodology: This is a product development research, given how the reality of access / accessibility of the population to the services and difficulties of the Dentists of the system. Results: The reorganization of the referral and consultation relationships between three different levels of attention on health units that have dentistry services of the administrative districts of the cities resulted the design of seven flowcharts, in accordance with organization, health services coverage and population-based research. As a result, could be quantify the coverage of basic care and number of health units per district. The different levels of attention addressed by the flowcharts aims to guarantee the integrality of the individual, promotion, protection and recovery in health, according to their need. Conclusions: The elaboration of the workflow seeks to promote effective access, which allows the right to health with better results in care resolution. The implementation will bring benefits both to the community and to the professionals of the unified health system.